Posterior Shoulder Instability in the Military and Athlete: An Evidence and Experience-Based Treatment Approach - Lance E. LeClere MD; Benjamin W. Hoyt MD; Kelly G. Kilcoyne MD; Jonathan F. Dickens MD (SAGE Publishing, 2023)
Background: Recognition of posterior glenohumeral instability has increased in young, athletic populations, leading to evolution in operative approaches to management. As with anterior instability surgery, successful treatment for these challenging injuries is dependent on understanding the key principles of pathology and restoration of the functional anatomy. Indications: Operative management of posterior glenohumeral instability is indicated for recurrent instability events or persistent pain refractory to physical therapy in the setting of posterior labral pathology with or without bone loss. Technique: In this video article, we present our approach to operative management of posterior glenohumeral instability in a young, athletic population, as developed through extensive experience in military and athlete populations and supported by research. Our approach to posterior glenohumeral instability is to restore the functional anatomy of the bone, labrum, and capsuloligamentous static restraints. We consider concomitant pathology and bone loss as components of these restraints that need to be restored to achieve a stable, painless shoulder. Using standard portals and tools, we prepare the glenoid and mobilize the labrum. When present, large osseous lesions can be restored using allograft distal tibia. We then repair and superiorize the inferior labrum, taking care to create a secure buttress against translation by positioning anchors at the edge of the chondral surface and everting the interior flap of tissue. If capsular pathology is present, this is also addressed. In the setting of significant posterior glenoid bone loss, we reconstruct the osseous support with a distal tibial allograft, which we perform arthroscopically and augment with labral repair. Using these techniques, surgeons can expect a low overall failure rate. In our young, highly active population, we observed 17.2% failure by 5 years, although this is dependent on multiple factors including age and bone loss. Discussion: Outcomes for posterior glenohumeral instability can be excellent with both nonoperative and operative treatments. When operative intervention is pursued, it is important to critically evaluate the anatomy, place portals considerately, and functionally restore the damaged structures. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.